The Silent Crisis: Malnutrition in Uttarakhand's Children - Pratiti Haldar; Lekha Viswanath; Ashok Kumar Srivastava; Alex James; Hem Chandra Sati (National Journal of Community Medicine)
Children comprise a major part of the population in many countries and are considered the future. A child is structured and designed right from birth by parents, school, society and environment into what they become. So, the foundation laid down in the young age plays an important role in the overall development of a child. A child’s development is influenced by various factor and one of the major issues is nutrition. Childhood nutrition is very important, and one cannot ignore the fact of adequate and appropriate nutrition for a child especially during the growing up days. Malnutrition is a major menace in many developing and underdeveloped countries, which places the children at risk to develop various other ailments. World Health Organization and Government of India have been trying to eliminate the peril of malnutrition by implementing various programs at various levels. In spite of the massive interventional programs at all levels the mortality rate of children dying because of malnutrition is still at alarming levels. The need to educate the masses at grass root levels is important and efficient screening is the need of the hour. For successfully eradicating malnutrition from our country, we all need to join in hands and pledge to make sure that our children are not deprived of proper nutrition, especially during the preschool age.